2005
DOI: 10.1590/s0103-84782005000600020
|View full text |Cite
|
Sign up to set email alerts
|

Indices ecodopplercardiográficos de função diastólica de gatos saudáveis não sedados

Abstract: O propósito deste estudo foi determinar os parâmetros de velocidades de ondas E e A, relação E/A, tempo de desaceleração da onda E e TRIV em gatos normais e não sedados, bem como correlacionar tais índices com a freqüência cardíaca. Estudaram-se 40 gatos hígidos, adultos, abrigados no gatil da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo. O exame foi realizado com os animais contidos em decúbito lateral esquerdo. Para cada parâmetro, obtiveram-se média, desvio padrão, mediana, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This relationship makes it possible to demonstrate changes in the speed of movement of the heart muscle [ 48 , 49 ]. Variations of these indexes beyond the limit of normality point to diastolic dysfunction and, depending on the pattern of abnormality, it can be inferred that the individual has impaired ventricular relaxation, that is, the active phase of diastole, or that he or she has less ventricular compliance/distensibility, in other words, of the passive phase of diastole [ 50 ]. Tissue Doppler ratio values (TD-l and TD-r) when <1 indicate diastolic dysfunction, which in this research did not happen after the administration of the protocols, therefore, there was no impairment of diastolic function with the drugs and doses that were used in both protocols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship makes it possible to demonstrate changes in the speed of movement of the heart muscle [ 48 , 49 ]. Variations of these indexes beyond the limit of normality point to diastolic dysfunction and, depending on the pattern of abnormality, it can be inferred that the individual has impaired ventricular relaxation, that is, the active phase of diastole, or that he or she has less ventricular compliance/distensibility, in other words, of the passive phase of diastole [ 50 ]. Tissue Doppler ratio values (TD-l and TD-r) when <1 indicate diastolic dysfunction, which in this research did not happen after the administration of the protocols, therefore, there was no impairment of diastolic function with the drugs and doses that were used in both protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Ansah et al, [34] concluded that the use of dexmedetomidine in cats at doses (25,50, and 75 μg/kg) induces, in a dose-dependent manner, sedation, analgesia, and clinically important muscle relaxation. An article comparing the use of dexmedetomidine alone or in combination with various opioids in healthy dogs reported that the sedative efects of dexmedetomidine were more pronounced when combined with a variety of opioids, particularly with butorphanol, meperidine, and methadone, compared with the sedative efects when dexmedetomidine was administered alone [35].…”
Section: Discussionmentioning
confidence: 99%